2005
DOI: 10.1029/2004ja010930
|View full text |Cite
|
Sign up to set email alerts
|

Overwhelming O+ contribution to the plasma sheet energy density during the October 2003 superstorm: Geotail/EPIC and IMAGE/LENA observations

Abstract: [1] We studied dynamics of O + ions during the superstorm that occurred on 29-31 October 2003, using energetic (9-210 keV/e) ion flux data obtained by the energetic particle and ion composition (EPIC) instrument on board the Geotail satellite and neutral atom data in the energy range of 10 eV to a few keV acquired by the low-energy neutral atom (LENA) imager on board the Imager for Magnetopause-to-Aurora Global Exploration (IMAGE) satellite. Since the low-energy neutral atoms are created from the outflowing io… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
88
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 88 publications
(99 citation statements)
references
References 41 publications
10
88
1
Order By: Relevance
“…[20] This result is somewhat surprising and diverges from recent observations, for example those reported by Nosé et al [2005] or Mitchell et al [2003]. From those results, and from the substantial contributions of oxygen in our earlier work on substorms and smaller storms [Fok et al, 2006;Moore et al, 2008], we anticipated that we might find that oxygen would essentially take over the ring current for such a large event, but that is not the case here.…”
Section: Discussioncontrasting
confidence: 56%
“…[20] This result is somewhat surprising and diverges from recent observations, for example those reported by Nosé et al [2005] or Mitchell et al [2003]. From those results, and from the substantial contributions of oxygen in our earlier work on substorms and smaller storms [Fok et al, 2006;Moore et al, 2008], we anticipated that we might find that oxygen would essentially take over the ring current for such a large event, but that is not the case here.…”
Section: Discussioncontrasting
confidence: 56%
“…The O + density close to the mid-latitude magnetopause was shown by Bouhram et al (2005) to also increase exponentially with Kp. A consequence of increased ion outflow is an enhancement of the plasma feed into the plasma sheet during geomagnetic storms (Nose et al, 2005;Kistler et al, 2010;Haaland et al, 2012). The plasma sheet in turn feeds the ring current and its relative O + content and energy density increases significantly with geomagnetic activity.…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of O + in terms of both number density and energy density increases with increasing geomagnetic activity ]. During extremely large storms, Nosé et al [2005] showed that the O + ions were dominant in the magnetotail plasma sheet [Zong et al, 2008] and the O + /H + energy density ratio was as large as 10-20, suggesting more than 90% of the total ring current energy density contributed from O + ions. It appears that the source and energization of O + ions are more responsive to disturbed activity than H + ions.…”
Section: Introductionmentioning
confidence: 99%